The impact of maternal nutrition on birth weight and brain development in children from low- and middle-income countries - Ringshaw, Jessica; Wedderburn, Catherine; Donald, Kirsten (My University, 2021)
Maternal nutrition is a key factor influencing optimal birth and child developmental outcomes. Although this is recognized globally, it is particularly relevant to low- and middle-income countries (LMICs) where the risk of malnutrition during pregnancy is high, and low birth weight (LBW) is prevalent. LBW has consistently been associated with poor health, stunted growth, and adverse neurocognitive outcomes. Less is known about the impact of maternal nutrition and LBW on neurodevelopment due to the limited focus of neuroimaging research on maternal obesity and pre-term birth in high-income countries. Maternal nutrition may be pivotal to understanding how LBW impacts the child brain in LMICs where there is a high risk of food insecurity and approximately 43% of children under the age of 5 are at risk of not reaching their developmental potential. Furthermore, examining the outcomes of LBW in babies who are small-for-gestational age (SGA) due to intrauterine growth restriction (IUGR) in LMICs is less-explored, yet important. Therefore, further neuroimaging research is needed to investigate the complex relationship between maternal nutrition, LBW and structural brain outcomes. This should be recognized as a research priority to inform nutritional interventions during pregnancy, and to optimize the developmental potential of children from LMICs.
Keywords: Birth Outcomes; Brain Development; Low Birth Weight; Maternal Nutrition; Neuroimaging